Case Report: A Novel Mutation in the CRYGD Gene Causing Congenital Cataract Associated with Nystagmus in a Chinese Family - Gao, Yunxia; Ren, Xiang; Fu, Xiangyu; Lin, Yu; Xiao, Lirong; Wang, Xiaoyue; Yan, Naihong; Zhang, Ming (Frontiers in Genetics, 2022)
Purpose: Congenital cataract (CC) is a common disease resulting in leukocoria and the leading cause of blindness in children worldwide. Approximately 50% of congenital cataract are inherited. Our aim is to identify mutations in a Chinese family with congenital cataract. Methods: A four-generation Chinese family diagnosed with congenital cataract were recruited in West China Hospital of Sichuan University. Genomic DNA was extracted from the peripheral blood of these participants. All coding exons and flanking regions were amplified and sequenced and the variants were validated using Sanger sequencing. AlphaFold2 was used to predict possible protein structural changes in this variant. Results: The proband had congenital nuclear cataract with nystagmus. A heterozygous variant c.233C > T was identified in exon 2 of the CRYGD gene in Chromosome 2. This mutation resulted in a substitution of Serine to Phenylalanine at amino acid residue 78 (p.S78F). The variant might result in a less stable structure with a looser loop and broken hydrogen bond predicted by AlphaFold2 and this mutation was co-segregated with the disease phenotype in this family. Conclusions: We described cases of human congenital cataract caused by a novel mutation in the CRYGD gene and provided evidence of further phenotypic heterogeneity associated with this variant. Our study further extends the mutation spectrum of the CRYGD gene in congenital cataract.